PENGARUH KUALITAS PRODUK DAN TINGKAT KEPUASAN KONSUMEN TERHADAP KEPUTUSAN PEMBELIAN SABUN MANDI MEREK LUX DI KALANGAN MASYARAKAT KOTA BANDA ACEH - Saed Armia (Pusat Penelitian dan Pengabdian Pada Masyarakat (P3M) STIES Banda Aceh, 2014)
Demand soap products in Banda Aceh to day is high enough. This is caused by the increase of population in the city of Banda Aceh , as well as the number of outstanding produ soap also from various kinds of products with different brands of bath soap bath soap in Banda Aceh , will cause confusion among buyers in choosing the type of oil that will consume , one brand of soap is quite popular among the people of Banda Aceh is lux soap and already have many customers and can be reached by the community in various circles . The purpose of this study was to determine whether kuaitas product , and the level of customer satisfaction bengaruh positive and significant impact on purchasing decisions lux toilet soap brand in the community in Banda Aceh , the object of this study is limited only to the quality of the product , the level of consumer satisfaction and purchasing decisions . Sampling was done with a probability sampling method with 100 respondents . The results showed that the quality of the product , and the level of customer satisfaction can affect purchase lux toilet soap brand in the community in Banda Aceh by 21.0 % . The results of this study indicate that the quality of the product , and the level of customer satisfaction , both simultaneously and partially significant effect on purchasing decisions lux brand soap products company among the people of Banda Aceh . Based on the research hypotheses proposed in this study an alternative hypothesis can be accepted, which means Ha accepted and ho rejected.